In vitro structural maturation of an early stage pre-40S particle coupled with U3 snoRNA release and central pseudoknot formation. Issue 20 (20th October 2022) - Cheng, Jingdong; La Venuta, Giuseppe; Lau, Benjamin; Berninghausen, Otto; Beckmann, Roland; Hurt, Ed
Abstract: The transition of the 90S to the pre-40S pre-ribosome is a decisive step in eukaryotic small subunit biogenesis leading to a first pre-40S intermediate (state Dis-C or primordial pre-40S), where the U3 snoRNA keeps the nascent 18S rRNA locally immature. We in vitro reconstitute the ATP-dependent U3 release from this particle, catalyzed by the helicase Dhr1, and follow this process by cryo-EM revealing two successive pre-40S intermediates, Dis-D and Dis-E. The latter has lost not only U3 but all residual 90S factors including the GTPase Bms1. In vitro remodeling likewise induced the formation of the central pseudoknot, a universally conserved tertiary RNA structure that comprises the core of the small subunit decoding center. Thus, we could structurally reveal a key tertiary RNA folding step that is essential to form the active 40S subunit.